Asal-usul Pembentukan Gunung Batur di daerah Wediombo, Gunungkidul, Yogyakarta - Gendoet Hartono; Sutikno Bronto (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no3.20073Physiographically, the Gunung Sewu Subzone is predominantly composed of limestone of the Wonosari Formation, but in Wediombo area volcanic rocks of the Wuni Formation is exposed. The Wediombo volcanic rocks contain lava flows and volcanic breccias associated with Batur intrusive rock, in which all the rocks have andesitic composition. The problem is whether the Wedi- ombo volcanic rocks originated from far distance area which then was intruded by local magma after its deposition, or it is an association of the Wediombo volcanic and the Batur intrusive rocks which both are the remnants of a paleovolcano in the area. To identify the central facies of the paleovolcano, the geological principle that “the present is the key the past” is used as a geological approach.Wediombo area forms a high landscape showing an elevation of about 280 m above sea level with dips of the outer slopes 20 - 40%. The drainage pattern developing in the area fol- lows the existing circular structure to form subradial - radial patterns. The high landscape shows a circular structure with a diameter of less than 2 km and it opens to the Indian Ocean. Besides the Mount Batur intrusive rock, there are some other dikes which have been already hidrothermally altered, with some mineralization in the circular structure. Meanwhile, the outer slopes are composed of alternating lava flows and fragmental volcanic rocks of 22 - 25o in dip forming a concentric pattern. Petrologically, the Batur intrusive rock is light to dark grey in color, hypocrystalline porphyritic texture, with phenocryst ranges from 1.2 - 2.2 mm in size, subhedral-euhedral crystals, fine vesicular structures. The rock comprises plagioclase, pyroxene, hornblende and opaque minerals. Geochemically, the rock indicates an island arc tholeitic magma (SiO = 60.38 – 64.53 wt%, K O = 0.63 – 0.85 wt%). Those data indicate that the circular structure was the central facies and the outer slope was the proximal facies of the Wediombo paleovolcano in Gunungkidul Yogyakarta.